Ensino superior e gênero: relação com o saber como perspectiva teórica - Teixeira, Karine Keily Rangel (2021)
The study discusses the entry and completion of women in higher education for a reflection about the female universe and the relationship with knowledge at university. It aims to propose a theoretical perspective on the relationship with knowledge and gender and adopts a systematic literature review with the search for articles in the Research Network on Relationship with Knowledge (REPERES). The results indicate a frequency of articles that deal with higher education in Brazil, and there are no studies on the theme presented here. It is concluded by the fertile possibility and relevance of studies about the approach of the relationship with knowledge and gender, by the possibility of expansion of the debates and the defense of gender equity in education and in the various fields of social life.